TНEORETICAL FOUNDATIONS OF THE SYSTEM OF STATE FINANCIAL SECURITY - Bezzubov, Dmitriy (Proceedings of National Aviation University (archive), 2016)
Purpose: The article the problem of formation of economic security. Disclosed principles, functions and methods of providing financial security. The ways of improving the mechanism of providing financial security. Methods: Formulate continuous logic in building the theoretical foundations of the system of financial security. It is shown that this idea may have the same conceptual framework: description, values, goals, mechanisms. Logic afford to provide clarity to ensure the integrity of financial security. Results: For economic growth and the successful functioning of the national economy neohidno a clear, stable, efficient tax system. The current tax system is an excessive burden for producers. Discussion: Aspects of the main approaches to the formation of a system of financial security of the state in terms of legal crisis and transformation vidchyznyanoho legislation. Definition of financial security as part of national security, which forms the economic direction counter threats.